The Impact of Mothers’ Media Literacy on the Media Education of Adolescents Aged 14-17 in District 5 of Tehran - Saeedfar, Parisa; Hejazi, Seyed Naser; Behyan, Shapour (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to determine the relationship between mothers’ media literacy and the media education of their children aged 14-17. Methods and Materials: The present study was a descriptive-analytical cross-sectional study. Multistage cluster sampling was conducted. A total of 249 students from public middle and high schools in District 5 of Tehran, who were enrolled in the 2022-2023 academic year, were selected. The demographic characteristics questionnaire, Tammen’s (1995) media literacy questionnaire, and a researcher-developed media education questionnaire were distributed, completed, and collected in compliance with research ethics. Data were analyzed using Pearson correlation, multiple regression analysis, t-test, and path analysis methods via SPSS 26 and PLS software. Findings: The correlation results indicated a statistically significant positive relationship at the 95% confidence level between mothers’ media literacy and the media education of high school students in District 5 of Tehran (r = 0.593, P < 0.05). A direct and significant relationship was found between consumption patterns and deep awareness (r = 0.357, P < 0.05) and responsible use (r = 0.380, P < 0.05). Additionally, there was a direct and significant relationship between message characteristics and deep awareness (r = 0.380, P < 0.05) and responsible use (r = 0.366, P < 0.05). A significant relationship was also observed between mothers’ ability to criticize message content and their children’s deep awareness (r = 0.283, P < 0.05) and responsible use (r = 0.109, P < 0.05). Conclusion: Mothers’ media literacy and its components (consumption patterns, message characteristics, and message critique) are recognized as influential variables in the media education of their children.